ATTENTION BIAS OF ANXIOUS YOUTH DURING EXTENDED EXPOSURE OF EMOTIONAL FACE PAIRS: AN EYE‐TRACKING STUDY. Issue 1 (19th July 2012) - Shechner, Tomer; Jarcho, Johanna M.; Britton, Jennifer C.; Leibenluft, Ellen; Pine, Daniel S.; Nelson, Eric E.
<x xml:space="preserve">Abstract</x> Background Previous studies demonstrate that anxiety is characterized by biased attention toward threats, typically measured by differences in motor reaction time to threat and neutral cues. Using eye‐tracking methodology, the current study measured attention biases in anxious and nonanxious youth, using unrestricted free viewing of angry, happy, and neutral faces. Methods Eighteen anxious and 15 nonanxious youth (8–17 years old) passively viewed angry‐neutral and happy‐neutral face pairs for 10 s while their eye movements were recorded. Results Anxious youth displayed a greater attention bias toward angry faces than nonanxious youth, and this bias occurred in the earliest phases of stimulus presentation. Specifically, anxious youth were more likely to direct their first fixation to angry faces, and they made faster fixations to angry than neutral faces. Conclusions Consistent with findings from earlier, reaction‐time studies, the current study shows that anxious youth, like anxious adults, exhibit biased orienting to threat‐related stimuli. This study adds to the existing literature by documenting that threat biases in eye‐tracking patterns are manifest at initial attention orienting.